A novel NKG2A alpaca nanobody targeting immune checkpoint blockade for the treatment of malignant melanoma - Guo, Xiang; Guo, Congfang; Li, Dongxiao; Bai, Yuting; Abbas, Mureed; Fan, Ruiwen; Zhao, Yiyan (Frontiers in Veterinary Science, 2025)
Alpacas belong to the Camelidae family. Antibodies produced through alpaca immunization are called nanoantibodies. Compared to traditional antibodies, nanoantibodies have several characteristics, including smaller molecular weight, stable structure, high homology with human antibodies, and suitability for prokaryotic expression. Malignant melanoma (MM) is a severe and aggressive form of cancer that affects both humans and animals. It commonly arises in the mucous membranes of the skin, nose, mouth, anus, and digestive tract, as well as in the choroid of the eyes. Multiple factors contribute to melanocyte carcinogenesis, including ultraviolet (UV) radiation, endocrine disorders, viral infections, immune deficiencies, and chemical carcinogens. At present, surgical resection remains to be the primary treatment for MM, although the prognosis is generally poor. However, targeted therapy and immune checkpoint inhibitors (ICIs) are increasingly employed in the clinical treatment of melanoma. NKG2A is an inhibitory receptor protein found on the surface of CD8+ T cells and natural killer (NK) cells. HLA-E ligands expressed on the surface of malignant melanoma cells can facilitate immune evasion by binding to the NKG2A receptor complex on immune cells. This interaction suppresses immune responses, enabling tumor cells to escape immune surveillance. Immunosuppressive antibody drugs work by blocking this recognition mechanism, thereby reactivating immune cells to target and destroy tumor cells. As such, NKG2A has emerged as a novel target for immunotherapeutic intervention. In this study, an alpaca-derived nanoantibody targeting NKG2A with high affinity was obtained from a melanoma-specific phage library display. Through induced expression and protein purification, a monoclonal nanobody strain expressing NKG2A was successfully isolated. This NKG2A-targeting nanobody demonstrates the potential for application in both the detection and treatment of MM.